2008
DOI: 10.1002/for.1119
|View full text |Cite
|
Sign up to set email alerts
|

Volatility forecasting with double Markov switching GARCH models

Abstract: This paper investigates inference and volatility forecasting using a Markov switching heteroscedastic model with a fat-tailed error distribution to analyze asymmetric effects on both the conditional mean and conditional volatility of financial time series. The motivation for extending the Markov switching GARCH model, previously developed to capture mean asymmetry, is that the switching variable, assumed to be a first-order Markov process, is unobserved. The proposed model extends this work to incorporate Mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The label switching phenomenon is a fundamental problem for MCMC estimation of the parameters of MS models; see Chen et al (2009). For identification, we use the following restriction to relabel the MCMC output to have higher intensity in state 2.…”
Section: Bayesian Inferencementioning
confidence: 99%
See 2 more Smart Citations
“…The label switching phenomenon is a fundamental problem for MCMC estimation of the parameters of MS models; see Chen et al (2009). For identification, we use the following restriction to relabel the MCMC output to have higher intensity in state 2.…”
Section: Bayesian Inferencementioning
confidence: 99%
“…The MS auto-regressive model that was introduced by Hamilton (1988) adopts the idea of regime variations in manifold economic and financial time series and continues to gain popularity in time series analysis, e.g. Cai (1994), Hamilton and Susmel (1994), Gray (1996) and Chen et al (2009). Zeger and Qaqish (1988) employed generalized linear models for the conditional distribution of an outcome given its past observations, calling them 'Markov regression models', in which they assumed that the intensity rate is a constant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the authors allowed for all volatility parameters to change across different states as well as the mean equation for the returns, allowing for more flexibility. Chen et al 57 showed that their proposed model is superior to standard approaches in VaR estimation. Define = ( 0 , 1 , , 2 , p, q) as a set of parameters associated with the volatility equation, = {( , 2 ) ( ) } ∞ =1 as a set of parameters associated with the distribution of the error term, and = ( , ) as a complete set of model parameters.…”
Section: Markov Switching Volatilitymentioning
confidence: 99%
“…The Markov switching model of Hamilton (1989) is widely used for time series in which the autoregressive parameters switch between different time regimes. Studies that implement HMMs include, among others, Hamilton (1990), Lahiri and Moore (1991), Lahiri and Wang (1994), Hamilton and Perez-Quiros (1996), Layton (1996), Gregoir and Lenglart (2000), Ivanova, Lahiri, and Seitz (2000), Marsh (2000), Kontolemis (2001), Koskinen and Öller (2003), Giampieri, Davis, and Crowder (2005), Andersson, Bock, and Frisén (2005), , Banachewicz, Lucas, and Vaart (2008), Chen, So, and Lin (2009), Parikakis and Merika (2009), Pinson and Madsen (2012), Nunes, Natário, and Carvalho (2013), Collet and Leonardi (2014), Dorosiewicz (2016), Hou (2017), Nystrup, Madsen, and Lindström (2017), and Nguyen (2018).…”
Section: Introductionmentioning
confidence: 99%